Gender Earning Gap and Higher Educational Attainment: Trends in Canada - Omar, Rozalina (AIUB Journal of Business and Economics, 2016)
The paper focuses on the relationship between the ongoing gender-earning gap and the increasing rate of higher educational attainment by women in Canada. The increasing rate of educational attainment allows women to enter several male-dominated professions, but in many cases women are not getting the expected returns compared to their male counterparts. Data shows that despite decades of anti-discrimination legislation and equal rights provisions in most peer countries, there is still a significant income gap between men and women in Canada which puts the increasing number of participation of women in tertiary education into a question. In this respect, the paper also includes some basic literature review to find out the reasons behind the gender pay gap. Overall, this paper concludes the necessity of narrowing gender-earning gap in order to achieve fair distribution of wealth.